Development of high-intensity ultrasonic wave surface cleaning - Tan, Wei Xin (Nanyang Technological University, 2021)
Ultrasonic cavitation is introduced to address the surface finishing of additive manufactured (AM) metal components with complex geometries. However, the commonly used bath type and horn type ultrasonicator have drawbacks of low cavitation intensity and high attenuation respectively leading to uneven surface finishing. To overcome the drawbacks, a newly customised high-intensity ultrasonic cavitation machine (HIUC) was developed to achieve high cavitation intensity with low attenuation effect for better performance. In this project, the cavitation intensity of the HIUC machine was studied using a hydrophone. Additionally, experiments were conducted on AM components to demonstrate the surface finishing effect on various geometries. The cavitation intensity was observed to be highest at the centre region of the tank due to the focusing effect of constructive wave interference at height of 200 mm from the bottom of the tank. The average surface roughness of additive manufactured Ti6Al4V and cobalt chrome were improved by around 10% and 22% respectively. Materials removal rate was increased found by significant mass loss after the cavitation process. The removal of metal powder particles attached to the specimen’s surface can also be observed directly via a scanning electron microscope (SEM).